Achievement of 17.9% efficiency in 30 × 30 cm2 Cu(In, Ga)(Se, S)2 solar cell sub‐module by sulfurization after selenization with Cd‐free buffer. (23rd July 2015) - Nam, Junggyu; Kang, Yoonmook; Lee, Dongho; Yang, JungYup; Kim, Young‐Su; Mo, Chan B.; Park, Sungchan; Kim, Dongseop
Abstract: We have achieved 17.9% efficiency in a 30 × 30 cm 2 Cu(In, Ga)(Se, S)2 solar cell sub‐module prepared by selenization and sulfurization processes with a Cd‐free buffer. The development of an absorber layer, transparent conducting oxide window layer, and module design was the key focus. This permitted 1.8% higher efficiency than our last experimental result. The quantity and the injection time of the sodium were controlled, resulting in higher open circuit voltage (Voc ) and short circuit current (Jsc ). In order to increase Jsc, we changed the thickness of the window layer. Boron‐doped zinc oxide was optimized for higher transmittance without reducing the fill factor. The uniformity of each layer was improved, and patterns were optimized for each module. Therefore, Voc, Jsc, and FF could be theoretically improved on the reported results of, respectively, 20 mV, 2 mA/cm 2, and 1.4%. The module's efficiency was measured at the Korea Test Laboratory to compare with the data obtained in‐house. Various analyses were performed, including secondary ion mass spectroscopy, photoluminescence, quantum efficiency, solar simulator, and UV–vis spectrometry, to measure the cell's depth profile, carrier lifetime, external quantum efficiency, module efficiency, and transmittance, respectively. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Seventeen point nine percent of high efficiency Cu(InGa)(SeS)2 solar cell was achieved by sputter and sequential process of selenization and sulfurization. Na addition encourages low temperature selenization and improves the crystal quality causing long carrier lifetime. High transmittance and low resistance transparent conducting oxide (B‐doped ZnO) layer was employed at CIGSSe sub‐module. High uniformity of absorber layer was also achieved by optimizing sputter condition and temperature profile of selenization/sulfurization process.